Empowering Students Through the Application of Self-Efficacy Theory in School Social Work: An Intervention Model - Nancy A Delich; Stephen D. Roberts (International Journal of School Social Work, 2017)
Self-efficacy is a construct well suited for social workers in the educational setting. Among the various job functions that school social workers assume, a large portion of their time is directed toward providing counseling and clinical services. Perceptions of self-efficacy are based upon the extent students expect to successfully attain their goals. Self-efficacious students with strong beliefs in their abilities will choose activities and social situations where they believe that they will be successful. Thus, they will be motivated to devote more time and effort toward accomplishing related goals. Conversely, inefficacious students of similar intelligence and capabilities may choose to abandon a challenging activity or social situation when they believe they will not be successful. The purpose of this paper is to describe a psycho-educational intervention model that school social workers can use to increase students’ self-efficacy. This article will first provide an overview of the theoretical foundations of Bandura’s self-efficacy theory. Included will be the four sources of influences used in formulating a person’s self-efficacy beliefs. Second, a self-efficacy intervention model will be introduced in which school social workers can counsel students to increase their self-efficacy. This intervention plan incorporates the four sources of Bandura’s self-efficacy training – enactive mastery experience, vicarious experience, verbal persuasion and physiologic and affective states. Third, a case example will be presented that illustrates the application of this intervention model with 12 deaf and hard of hearing high school students who experienced bullying in one California school district.
Keywords: school social work; counseling; deaf and hard of hearing students; mastery experience; self-efficacy